Early esophageal cancer diagnosis in Central Oromia, Ethiopia: patient and provider perspectives on barriers and facilitators - Teresa Kisi Beyen; Edom Seife; Biniyam Tefera Deressa; Girma Taye; Adamu Addissie (Scientific Reports, 2026)
Abstract In Ethiopia, 70–90% of esophageal cancer patients are diagnosed at advanced stages (III and IV), with the highest burden in Oromia’s Arsi and Bale zones. Despite the burden of esophageal cancer, little is known about the factors influencing its early diagnosis in Central Oromia. This qualitative study sought to address this gap by exploring barriers and facilitators from the perspectives of both patients diagnosed at late stages and healthcare providers. Between August 17 and September 26, 2025, in-depth interviews were conducted using an exploratory case study design with 13 late-stage esophageal cancer patients and 11 healthcare providers across four Ethiopian hospitals. Participants were recruited from the hospitals using criterion sampling, and all were residents of Central Oromia, specifically Arsi, West Arsi, Bale, East Bale, and East Shewa, until data saturation was achieved. Inductive thematic analysis was performed using MAXQDA (version 24.4.1). Five main themes emerged: patient-related factors, health system-related factors, policy and strategy-related factors, emotional and ethical challenges in care, and research and evidence gaps. Late presentation and delayed health-seeking, reliance on traditional and religious care, Cancer-related fear, stigma, and fatalistic beliefs, limited awareness and education, financial constraints, geographic inaccessibility, misdiagnosis, referral system dalliance and complexities, diagnostic service limitations, workforce shortages, insufficient government support, absence of contextual screening frameworks, and research and evidence gaps were barriers to early esophageal cancer. In contrast, facilitators comprised family influence and support, health insurance coverage, and multidisciplinary and integrated cancer care. Delayed diagnosis in Central Oromia resulted from complex, multi-level factors. Addressing these barriers requires a comprehensive strategy including public awareness campaigns, healthcare provider training, improved referral systems, and expanded access to affordable, decentralized diagnostic services. Context-specific interventions are essential to facilitate earlier diagnosis and improve survival outcomes for esophageal cancer patients in central Oromia and similar Ethiopian settings.